Thermodynamic calculations of the polybaric melting phase relations of spinel lherzolite. (29th December 2014) - Ueki, Kenta; Iwamori, Hikaru
Abstract This study presents a new thermodynamic model for the calculation of phase relations during the melting of anhydrous spinel lherzolite at pressures of 1–2.5 GPa. The model is based on the total energy minimization algorithm for calculating phase equilibria within multicomponent systems and the thermodynamic configuration of Ueki and Iwamori [2013]. The model is based on a <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh39c321gv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />SiO2−Al2O3−FeO−Fe3O4−MgO–CaO</alternatives> system that includes silicate melt, olivine, clinopyroxene, orthopyroxene, and spinel as possible phases. The molar Gibbs free energy of the melt phase is modeled quasi‐empirically, and the thermodynamic parameters for silicate melt end‐member components are calibrated with a polybaric calibration database. The temperatures and pressures used in this newly compiled calibration data set are 1230–1600°C and 0.9–3 GPa, corresponding to the stability range of spinel lherzolite. The modeling undertaken during this study reproduces the general features of experimentally determined melting phase relations of spinel lherzolite at 1–2.5 GPa, including the solidus temperature, the melt composition, the chemical reaction during melting, and the degree of melting. This new thermodynamic modeling also reproduces phase relations of various bulk compositions from fertile to deplete spinel lherzolite and can be used in the modeling of polybaric mantle melting within various natural settings. Comparing the results derived from this new modeling with those produced using previous models indicates that the new approach outlined here, involving a combination of total energy minimization and the direct calibration of melt thermodynamic parameters at pressure and temperature conditions corresponding to mantle melting with a relatively simple melt thermodynamic equation, can accurately model polybaric melting phase relations.